Respuesta :
Answer:
[tex]h = - 12[/tex]
Step-by-step explanation:
1) Add 1 to both sides.
[tex] \frac{h}{6} = - 3 + 1[/tex]
2) Simplify -3 + 1 to -2.
[tex] \frac{h}{6} = - 2[/tex]
3) Multiply both sides by 6.
[tex]h = - 2 \times 6[/tex]
4) Simplify 2 × 6 to 12.
[tex]h = - 12[/tex]
Therefor, the answer is h = -12.
Answer:
h = - 12
Step-by-step explanation:
Add 1 to both sides of the equation
ℎ/6 − 1 + 1 = − 3 + 1
Simplify
ℎ/6 = − 3 + 1
h/6 = -2
Multiply all terms by the same value to eliminate fraction denominators
6 ⋅ ℎ/6 = 6 ( − 2 )
Cancel multiplied terms that are in the denominator
ℎ = 6 ( − 2 )
Multiply the numbers
ℎ = − 12